5x-2(x-5)=-4+5x+8

Simple and best practice solution for 5x-2(x-5)=-4+5x+8 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x-2(x-5)=-4+5x+8 equation:


Simplifying
5x + -2(x + -5) = -4 + 5x + 8

Reorder the terms:
5x + -2(-5 + x) = -4 + 5x + 8
5x + (-5 * -2 + x * -2) = -4 + 5x + 8
5x + (10 + -2x) = -4 + 5x + 8

Reorder the terms:
10 + 5x + -2x = -4 + 5x + 8

Combine like terms: 5x + -2x = 3x
10 + 3x = -4 + 5x + 8

Reorder the terms:
10 + 3x = -4 + 8 + 5x

Combine like terms: -4 + 8 = 4
10 + 3x = 4 + 5x

Solving
10 + 3x = 4 + 5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-5x' to each side of the equation.
10 + 3x + -5x = 4 + 5x + -5x

Combine like terms: 3x + -5x = -2x
10 + -2x = 4 + 5x + -5x

Combine like terms: 5x + -5x = 0
10 + -2x = 4 + 0
10 + -2x = 4

Add '-10' to each side of the equation.
10 + -10 + -2x = 4 + -10

Combine like terms: 10 + -10 = 0
0 + -2x = 4 + -10
-2x = 4 + -10

Combine like terms: 4 + -10 = -6
-2x = -6

Divide each side by '-2'.
x = 3

Simplifying
x = 3

See similar equations:

| 2x+(-1/2x-1)=2 | | -9y=2.52 | | 26(-17)+15(-22)= | | 2n+12=36 | | (5v-7)*(2v+9)=0 | | 9x-4=293 | | -7-6x=14+9x | | 5x+14=113-6 | | 5x-(x-5)=-4+5x+8 | | 20+(-9)(-15)+-2= | | 1.005=0.95+0.005x | | 39x+33=462 | | (p-q)*(r-s-t)=0 | | 80-2x=56 | | 4x^(3/2)=16 | | 2(t-3)-3=7 | | (-4y+x-7)*x=0 | | x+4/3=x+6/5 | | 6[-3+7(-2+5)]= | | 3x+2xy+8=0 | | (2x+1)(2x-1)=3 | | (3x-2y+4)-(-6x+y-5)=0 | | (-2-2)[8+(7+8)]= | | (3x-2y+4)+(-6x+y-5)=0 | | 3x+5xy=8 | | y=7sin(x^2) | | x^2-50x+576=0 | | (5r+2s-t)-(-3r-s+6t)=0 | | (-15-2)(-20-7)= | | x+2x+(x+3)=7 | | 14-w=42 | | (11p-7q-r)+(3p+q-9r)+(-p-q+2r)=0 |

Equations solver categories